Optimising tibial extension stem selection in total knee arthroplasty: the role of digital modelling - Severyns, Mathieu; Zot, François; Gardegaront, Marc; Germaneau, Arnaud; Vendeuvre, Tanguy (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study explores the biomechanical impact of tibial extension stems in total knee arthroplasty using finite element digital modelling. The objective is to enhance stem selection by assessing stress and strain distribution in periprosthetic bone under varied loading scenarios.MethodsSix patient-specific FE models were created, each with different stem dimensions, to evaluate how stem geometry affects implant stability and fracture risk.ResultsExtension stems reduce strain under the tibial baseplate but increase stress and fracture risk in the surrounding bone, particularly at the stem tip. Larger stem diameters were linked to higher fracture risks due to increased press-fit contact.ConclusionThese findings are consistent with previous research emphasizing the importance of stem design in achieving a balance between implant stability and bone preservation. The study offers a biomechanical foundation for surgical planning, potentially improving TKA durability and functional outcomes. Incorporating these insights into clinical practice may enhance the longevity of knee replacements and overall patient quality of life.